2006
DOI: 10.1080/09553000600733168
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of the SOS Chromotest in the study of medicinal plants as radioprotectors

Abstract: The results have demonstrated the usefulness of the modified SOS Chromotest assay in the screening of phytochemical radioprotectors as well as in the study of their antimutagenic mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 50 publications
0
6
0
1
Order By: Relevance
“…We have previously proposed the SOS chromotest as a potentially useful assay for primary screening of medicinal plant extracts for antigenotoxic activity against γ-rays (Fuentes et al , 2006a). With this test, we have observed that the use of DMSO as solvent resulted in overestimates of the antimutagenic activity of essential oils when compared with distilled water (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously proposed the SOS chromotest as a potentially useful assay for primary screening of medicinal plant extracts for antigenotoxic activity against γ-rays (Fuentes et al , 2006a). With this test, we have observed that the use of DMSO as solvent resulted in overestimates of the antimutagenic activity of essential oils when compared with distilled water (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…This assay, which is based on a colorimetric assessment of SOS transcriptional gene fusion in Escherichia coli PQ37, allows one to estimate primary DNA damage produced by chemical and physical mutagens by measuring the expression of a reporter gene, β-galactosidase (Quillardet and Hofnung, 1993). Compared to other methods, the SOS chromotest allows greater throughput when screening natural compounds (Fuentes et al , 2006a). …”
Section: Introductionmentioning
confidence: 99%
“…However, the presence of POE significantly protected DNA molecules from CPD formation and UVB-ROS generation. For this extract free oxygen radical scavenging activity, was previously demonstrated, which contributes to UVB-photooxidative protective effect [5,[17][18][19][20]. According to the UVB transmittance of CF and DF, none of these fractions protected DNA against the damages induced by UVB light.…”
Section: Discussionmentioning
confidence: 99%
“…Similar modifications were also introduced to the SOS chromotest (Ohta et al, 1984). The original colorimetric procedure of the assay (Quillardet et al, 1982) was successfully changed to a fluorimetric one by using the fluorescent substrate 4-methylumbelliferyl-b-Dgalactopyranoside (MUG) (Fuentes et al, 2006).…”
Section: Reporter Systemsmentioning
confidence: 99%